Stochastic methods in finance lectures - Frittelli M ed.; C.I.M.E.-E.M.S. Summer School on Stochastic Methods in Finance; C.I.M.E.-E.M.S. summer school on stochastic methods in finance Brixen, Italy 6-12 Jul 2003 (Berlin Springer-Verlag, 2004)
This volume includes the five lecture courses given at the CIME-EMS School on Stochastic Methods in Finance held in Bressanone/Brixen, Italy 2003. It deals with innovative methods, mainly from stochastic analysis, that play a fundamental role in the mathematical modelling of finance and insurance: the theory of stochastic processes, optimal and stochastic control, stochastic differential equations, convex analysis and duality theory. Five topics are treated in detail: Utility maximization in incomplete markets; the theory of nonlinear expectations and its relationship with the theory of risk measures in a dynamic setting; credit risk modelling; the interplay between finance and insurance; incomplete information in the context of economic equilibrium and insider trading.
Keywords: Applied statistics; Financial economics; Stochastic processes